Innovation of A Smart Dental Mirror for More Effective and Efficient Plaque Score Assessment - Fernanda, Fradita; Supriyana, Supriyana; Suwondo, Ari (MEDICA (International Medical Scientific Journal), 2026)
Dental plaque is one of the primary etiological factors contributing to oral diseases. Therefore, plaque detection and control are essential components of preventive dental care. Conventional plaque detection methods using disclosing agents still present several limitations, including chemical content, complicated application procedures, subjective interpretation, and potential side effects on oral tissues. Consequently, technological innovation is needed to improve the effectiveness and efficiency of plaque examination. This study aimed to develop and evaluate a smart dental mirror based on camera technology and deep learning sensors as an innovative tool for plaque assessment. The study employed a Research and Development (R&D) approach with a quasi-experimental crossover design. A total of 33 dental health professionals were recruited using purposive sampling. Product testing was conducted to evaluate the effectiveness and efficiency of plaque examination through observation and interview methods. Data were analyzed descriptively and statistically using the Wilcoxon test. The results of expert validation showed that the smart dental mirror achieved a feasibility score of 72.2%, indicating that the device was suitable for use. The effectiveness test demonstrated no statistically significant difference between the smart dental mirror and the conventional method (p = 0.439), indicating comparable effectiveness in plaque assessment. However, the efficiency test revealed a statistically significant difference (p = 0.001), indicating that the smart dental mirror provided greater efficiency compared to the conventional method. In conclusion, the smart dental mirror is considered a feasible, efficient, and innovative alternative for dental plaque assessment, with effectiveness comparable to conventional methods while offering improved operational efficiency in clinical practice.